Fewpal
0 votes
21 views
in Computer by (15 points)

Please log in or register to answer this question.

1 Answer

0 votes
by (71 points)
xy + y( z+z' ) = xy + y          .....( ∵ x+x' = 1 in boolean algebra )

==> y ( x + 1 ) = y              .....(  ∵ x+1 = 1 in boolean algebra )

==> Hence LHS = RHS

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...